Interview-based cross-sectional needs assessment to advance the implementation of an effective antibiotic stewardship program in Indonesian hospitals - Fauna Herawati; Sheny Clarin Ananta; Ida Ayu Andri Parwitha; Sylvan Septian Ressandy; Nur Laili Rahmatin; Nur Afifah Rachmadini; Veronika Ayu Tangalobo; Setiasih; Rika Yulia; Eelko Hak; Herman J. Woerdenbag; Christina Avanti (Elsevier, 2020)
Antibiotic resistance has become a global health issue, negatively affecting the quality and safety of patient care, and increasing medical expenses, notably in Indonesia. Antibiotic stewardship programs (ASPs) aim to reduce resistance rates and their implementation in hospitals, has a high priority worldwide.We aimed to monitor the progress in the organizational implementation of ASPs in Indonesian hospitals by an Antimicrobial Resistance Control Program (ARCP) team and to identify possible hurdles. We conducted a cross-sectional study with structured interviews based on a checklist designed to assess the achievement of structural indicators at the organizational level in four private and three public hospitals in four regions (Surabaya, Sidoarjo, Mojokerto, Bangil) in East Java, Indonesia.The organizational structure of public hospitals scored better than that of private hospitals. Only three of the seven hospitals had an ARCP team. The most important deficiency of support appeared to be insufficient funding allocation for information technology development and lacking availability and/or adherence to antibiotic use guidelines. The studied hospitals are, in principle, prepared to adequately implement ASPs, but with various degrees of eagerness. The hospital managements have to construct a strategic plan and to set clear priorities to overcome the shortcomings.